2007
DOI: 10.1016/j.chiabu.2007.04.008
|View full text |Cite
|
Sign up to set email alerts
|

The association between maltreatment and obesity among preschool children

Abstract: Objective-To determine whether child maltreatment is associated with obesity in preschool children.Methods-Data were obtained from the Fragile Families and Child Wellbeing Study, a birth cohort study of 4898 children born between 1998 and 2000 in 20 large US cities. At 3 years of age, 2412 of these children had their height and weight measured, and mothers answered items on the ParentChild Conflict Tactics Scales about three types of child maltreatment-neglect, corporal punishment, and psychological aggression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
72
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 31 publications
6
72
2
Order By: Relevance
“…Yet our finding contrasts with those reported by Gooding et al (2015) and Whitaker et al (2007), where emotional abuse was not significantly associated with child or adolescent BMI. Given these contradictory findings, future studies, and perhaps a meta-analytic review, will be necessary to substantiate the association.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Yet our finding contrasts with those reported by Gooding et al (2015) and Whitaker et al (2007), where emotional abuse was not significantly associated with child or adolescent BMI. Given these contradictory findings, future studies, and perhaps a meta-analytic review, will be necessary to substantiate the association.…”
Section: Discussioncontrasting
confidence: 57%
“…In contrast, Schneiderman, Mennen, Negriff, and Trickett (2012) reported an unexpected inverse association of physical abuse victimisation and obesity in adolescent girls. In two studies with younger children, Burke et al (2011) showed that overall adverse childhood experiences (including emotional, physical, and sexual abuse, along with other non-abusive stressors) predicted greater BMI in 8-year-olds, but Whitaker et al (2007) found no relation between preschoolers' obesity and either corporal punishment or psychological/emotional (e.g., name calling; threats) parent-to-child aggression.…”
mentioning
confidence: 99%
“…Much research has been undertaken to study the link between any one individual factor and obesity. [6][7][8][9][10][11][12][13][14] For example, metabolic risk factors such as diabetes have been shown to be linked to obesity, and there is growing research exploring the associations between chemical exposures and diabetes. 15,16 However, the inter-relationships between stressors are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…The literature has focused especially on violence in childhood or adolescence and its repercussions during this same phase of life or later, in adulthood. Although the findings are still limited, they point to a direct statistical association between violence and overweight/obesity 11,12,13 . The main assumption of such studies is that suffering abuse oneself and witnessing intimate partner violence during childhood and adolescence trigger various mental health problems and lead to excessive consumption of high energy-density foods and reduced physical activity, lifestyles that can last into adulthood 13,14 .…”
Section: Introductionmentioning
confidence: 99%